1998
DOI: 10.1215/03616878-23-2-215
|View full text |Cite
|
Sign up to set email alerts
|

Economists, Public Provision, and the Market: Changing Values in Policy Debate

Abstract: Among health services researchers, an "economizing model" of health care has eclipsed two traditional models, "social conflict" and "collective welfare." The older models emphasized social solidarity and distributive justice, but the newer one focuses on improving efficiency, minimizing risks borne by third-party payers, constraining cost increases, and improving the functioning of markets. This article examines one source of the economizing model, the work of several early and persistently prominent economist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Because chronic patients often occupied acute‐care beds, experts saw chronic care rendered in acute settings as unnecessarily expensive and ill suited to patients' needs, and they found physicians little interested in chronic disease. However, major medical insurance, which emerged after the war, paid for some chronic‐care services (Melhado 1998, 231–33). To exploit the new funds and efficiently meet patients' needs, planners applied their vision of rural hierarchy to the urban setting: they anticipated a tight cluster of coordinated facilities and services, that is, a medical center (Brown 1968b; Haldeman 1962b, 1963, 47, 1966, 1967; Morris 1963b).…”
Section: The Antecedentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because chronic patients often occupied acute‐care beds, experts saw chronic care rendered in acute settings as unnecessarily expensive and ill suited to patients' needs, and they found physicians little interested in chronic disease. However, major medical insurance, which emerged after the war, paid for some chronic‐care services (Melhado 1998, 231–33). To exploit the new funds and efficiently meet patients' needs, planners applied their vision of rural hierarchy to the urban setting: they anticipated a tight cluster of coordinated facilities and services, that is, a medical center (Brown 1968b; Haldeman 1962b, 1963, 47, 1966, 1967; Morris 1963b).…”
Section: The Antecedentsmentioning
confidence: 99%
“…In the view of market advocates, the failures of past policy reflected the failures of the culture of policymaking that sought to limit the reach of market mechanisms and to substitute professional for consumer judgment and, paradoxically, cited the failure of markets in justifying a regulatory approach to health affairs. This article will not analyze the onslaught against the collective‐welfare and social‐conflict models for advocacy and research in health policy (Fox 1990, 1995; Goldsmith 1984; Melhado 1988, 1998; Schramm 1988), but just observe that critics traced the problems of health care to practices that, despite (or even because of) reformers' efforts, locked in the power of health care interests. Moreover, the motives of health care professionals and policy experts grew suspect, both because the critics of social‐trustee professionalism portrayed professionals as selling services to employers and other interested parties rather than protecting collective values (Brint 1994) and because in fact health care experts increasingly found employment in a wider variety of settings, serving as agents for private interests with major economic stakes in health care (Fox 1990).…”
Section: Concluding Reflectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since insurance premiums are partially based on the volume of services consumed, overuse makes the system more expensive for everyone. Concern with efficiency, runaway costs, and overuse came to dominate health policy in the 1970s in what has been dubbed ''economism,'' largely because of the influence of economists like Mark Pauly and new empirical data about cost sharing and plan designs stemming from the Rand studies (Fox 1990;Frankford 1994;Melhado 1998;Nyman 2007). Proponents of economism concluded that more competitive health care markets, increased cost sharing, and utilization controls were not only necessary but socially beneficial in the fight to curb overuse.…”
Section: Introductionmentioning
confidence: 99%